National Science Center / Nurul Syazwani Rusdi - Rusdi, Nurul Syazwani (Faculty of Business and Management, 2023)
This report is prepared for the Internship phase of HRM666 program of Universiti Teknologi MARA. This Internship Program as well as this report is an indispensable of my course of Bachelor of Business Administration (Hons.) Human Resource Management. After completion of my course in the different areas of studies, students are sent to different reputed Business organization to acquire the real-life experience. So, I was placed in National Science Center at Kuala Lumpur to understand the Human Resource Performance. The industrial training report has been prepared based on experience gathered during the period of internship which has been started on 1st March 2023 until 15th August 2023. For preparing the report, I have also got the information from staff and my supervisor in National Science Center. It helps a lot to gain more knowledge that will be share in this report about National Science Center. This report focuses six months working experiences in National Science Center. This report will give a clear idea about activities, product and services and operational strategies of National Science Center. Especially this report focuses on human resource performance of National Science Center. The report will provide a clear conception about the Human Resource Performance and this report contains nine parts. The first part of the report is preliminary pages, second is student’s profile, third is company’s profile, forth is training’s reflection, fifth is SWOT analysis and the sixth is discussion and recommendation. Next is followed by conclusion, refences and appendices. This is the knowledge that will gain from National Science Center to others well known and have interest to visit National Science Center.